Concentrations of bisphenols, benzophenone-type ultraviolet filters, triclosan, and triclocarban in the paired urine and blood samples from young adults: Partitioning between urine and blood. (February 2022) - Zhang, Hua; Li, Jingxia; An, Yulin; Wang, Desheng; Zhao, Jianfu; Zhan, Meixiao; Xu, Weiguo; Lu, Ligong; Gao, Yunfei
Abstract: Bisphenols (BPs), benzophenone-type UV filters (BP-type UV filters), triclosan (TCS), and triclocarban (TCC) are endocrine-disrupting chemicals (EDCs) and commonly used in consumer and personal care products. In the present study, seven BPs, eight BP-type UV filters, TCS, and TCC were quantified in 196 paired urine and blood samples collected from young adults in South China. Benzophenone-7 and benzophenone-9 were not detected in all samples, while other target compounds were widely detected in 39%–96% of the urine and 14%–96% of the blood samples, and the median concentrations ranged from <0.02 (specific gravity adjusted: < 0.02) to 2.33 (2.05) ng/mL and <0.01–2.66 ng/mL in the urine and blood samples, respectively. Females had higher levels of most target analytes, and gender-related differences ( p  < 0.05) were found in the blood levels of benzophenone-2 (females vs. males: 0.84 vs. <0.01 ng/mL), ΣBP (sum of BP-type UV filters; 1.61 vs. 0.98 ng/mL), TCS (3.89 vs. 1.69 ng/mL), and ΣTC (sum of TCS and TCC; 5.77 vs. 3.02 ng/mL). We calculated the portioning of the target compounds between blood and urine (B/U ratios). The B/U ratios of bisphenol F, benzophenone-2, benzophenone-6, 4-hydroxy benzophenone, TCS, and TCC were higher than 1, showing that these analytes have higher enrichment capacities in human blood. To the best of our knowledge, this is the first study to simultaneously analyze the concentrations of BPs, BP-type UV filters, TCS, and TCC in the paired urine and blood samples of young adults in South China. Graphical abstract: Image 1 Highlights: First study of urinary and blood BPs, BP-type UV filters, TCS, and TCC levels in Chinese young adults. Gender-related difference in levels of BP-type UV filters, TCS, and TCC were found. BPF, BP-2, BP-6, 4-OH-BP, TCS, and TCC have higher enrichment capacity in human blood.